Democratic Republic of the Congo : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Waiver of Performance Criteria and Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2004)
This paper discusses Congo's Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and Requests for Waiver of Performance Criteria. Overall performance under the program was satisfactory and at end-March 2004, 8 out of the 11 quantitative performance criteria were observed. The structural performance criterion was met. Economic growth has been higher than envisaged, and inflation has decelerated more rapidly than programmed. As expected, the end-2003, fiscal objectives were missed by less than 1 percent of GDP.